Brays and bits: Information theory applied to acoustic communication sequences of bottlenose dolphins - Luís, Ana Rita (2018)
Acoustic call sequences are important components of vocal repertoires for many animal species. Bottlenose dolphins (Tursiops truncatus) produce a wide variety of vocalizations, in different behavioural contexts, including some conspicuous vocal sequences – the ‘bray series’. The occurrence of brays is still insufficiently documented, contextually and geographically, and the specific functions of these multi-unit emissions are yet to be understood. Here, acoustic emissions produced by bottlenose dolphins in the Sado estuary, Portugal, were used to provide a structural characterization of the discrete elements that compose the bray series. Information theory techniques were applied to analyse bray sequences and explore the complexity of these calls. Log-frequency analysis, based on bout criterion interval, confirmed the bout structure of the bray series. A first-order Markov model revealed a distinct pattern of emission for the bray series’ elements, with uneven transitions between elements. The order in these sequential emissions was not random and consecutive decreases in higher order entropy values support the notion of a well-defined structure in the bray series. The key features of animal signal sequences here portrayed suggest the presence of relevant information content and highlight the complexity of the bottlenose dolphin’s acoustic repertoire.